AMENDMENTS TO THE ORTHOGRAPHY OF MATICA SRPSKA IN TEACHING SERBIAN IN EXTRA CLASSES IN SECONDARY SCHOOLS - Ивана Ђ. Ђорђев (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2012)
In this paper, based on relevant methodological and contemporary normative literature, a methodological model suitable to perform the additional hours of teaching the Serbian language and literature in the fourth year of high school is developed. The aim of this paper is to review some of the amendments to the current Orthography of Serbian language by Matica srpska and contribute to faster and easier adoption of innovations primarily established for the written expression of students in secondary education. A model of differentiated instruction has been carried out in teaching practice, as well as at regular meetings of a secondary linguistic club. This contributed to the enrichment of studentsʼ overall language culture and influenced a greater interest of students in other topics of this very important segment of language teaching.